Fibre Bragg grating based system for real-time railway monitoring - Li Jing (2015)
Fibre Bragg grating (FBG) sensor technology has created considerable interest in both academic institutions and industrial sectors over the past few years. In particular, there are potentially huge benefits to transportation industry especially the railways. The safety, stability, cost and multiple-functionality requirements make the task of understanding the operational and structural conditions of trains and rails daunting. FBG sensors, a unique type of optic sensors offer immunity to Electromagnetic Interference, very long distance interrogation, long life-span and multiplexing capacity over conventional electrical sensors so as to meet all the above challenges. Past studies have proven that FBG sensors are helpful in the tasks of axle counting, track and train vibration monitoring, monitoring of structural health of the train and the track. These studies demonstrated the possibility of larger scale implementation of FBG sensors. In this project, FBG sensors are installed on the railway model for the purpose of sensing the strain. The reflected light’s wavelength data are transmitted to a specifically designed program in the customized user interface through FBG interrogator. This program subsequently analyses the wavelength data and generates suitable responses to various railway conditions to achieve the functions of real-time train positioning, speeding alert and overloading notification.